Legal and financial liability in healthcare — selected issues - Lenio, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
This study addresses the issue of liability for infringing public finance discipline in the healthcare sector. The subjective and objective scope of this type of liability was examined with reference to the Polish healthcare system. The author assessed selected acts constituting violations of public finance discipline relevant to the finances of this system. It was also established that the subjective and objective scope of liability was shaped without taking into account the specifics of the functioning of the public healthcare sector. There are, however, two exceptions that have been analysed in detail in this study.
Keywords: public finance discipline; healthcare